Use of CHROMagar Candida for genital specimens in the diagnostic laboratory. Issue 7 (July 1997) - Houang, E T; Chu, K C; Koehler, A P; Cheng, A F
Abstract : OBJECTIVE: To evaluate CHROMagar Candida (CA), a new yeast differential medium, for yeast isolation in a clinical laboratory for the routine examination of high vaginal swabs. METHODS: Results of high vaginal swab cultures processed in a standard manner on plates containing equal halves of Sabouraud dextrose agar (SDA) and CA were compared. Non-Candida albicans yeast isolates were further speciated with API 20C AUX or API 32C. To assess the ease of use of CA, laboratory staff lacking in experience of the medium were asked to identify 23 unlabelled yeast cultures on CA by referring to six labelled reference plates. RESULTS: Of the 1784 swab cultures processed, yeasts were isolated from 373 SDA and 368 CA. Of the 78 non-albicans isolates further speciated, CA identified correctly all cultures of C krusei and C tropicalis, and 82% of C glabrata. All the 38 inexperienced laboratory staff achieved 100% accuracy for C albicans and over 90% for C krusei and C tropicalis. CONCLUSIONS: CA is a satisfactory isolation medium for genital specimens, allowing immediate and correct identification of the commonly encountered yeasts and easy recognition of mixed cultures.